Bio-Oil Model Compounds Upgrading Under CO Atmosphere - Xu1, Qingli; Dai1, Weidi; Jiang1, Jianchun; Yan2, Yongjie (Asian Journal of Chemistry, 2014)
The bio-oil model upgrading was studied over a series of catalysts in the CO/H2O system. The impregnation method was superior to the dry mix method. 6 % of Ni impregnating in B206 catalyst is the optimum bi-functional catalyst. The optimum catalyst showed the highest activity for deoxygenation in the CO/H2O system, the deoxygenation rate was up to 92 % and the dehydration rate was 89 % in a certain conditions after upgrading.